TIDAK DITERAPKANNYA PASAL 362 KUHP DALAM PERKARA PENAMBANGAN TANPA IZIN (STUDI PUTUSAN NOMOR 124/PID.SUS/2021/PN. TDN) - Achmadi, Cika Artika (Universitas Muhammadiyah Ponorogo, 2023)
Mining activities cannot be carried out haphazardly because every business entity or individual must have a mining permit. Anyone who engages in illegal mining will be subject to sanctions in accordance with Article 158 of Law Number 3 of 2020 concerning